Competition rule of the multi-criteria approach: what contractors in China really want? - Ye, Kunhui; Zeng, Dan; Wong, Johnny (Journal of Civil Engineering and Management, 2018)
Recent years have witnessed the diversifying means of competitive bidding, where the client plays a critical role in the determination of competition rule. It is widely recognized that the competition rule should be placed on a win-win basis to ensure that both the client and contractors are well considered with respect to their interests. Nevertheless, a vast majority of biddings fail to take account of what contractors really want. Using the methods of literature review and content analysis, 34 tender evaluation factors are proposed to compose the competition rule in China. Contractors’ opinions on these factors are collected by virtue of questionnaire survey. Based on the Pareto law, it is found that the competition rule encompasses eleven key factors, and the composition varies slightly between public and private sectors. The Hotelling’s T test is conducted on those key factors in common. The implication is that contractors can use indifferent factors (e.g., credit rating, construction plan, completeness of bid components, timely payment to workers) to improve competitiveness, while the client may utilize different factors to diversify the competition rule. This paper probably presents an earliest effort put to examine the acceptability of competition rule in the construction context.